Are Caudal Blocks for Pain Control Safe in Children? An Analysis of 18, 650 Caudal Blocks From the Pediatric Regional Anesthesia Network (PRAN) Database. Issue 2 (April 2016) - Suresh, Santhanam; Long, Justin; Brimingham, Patrick K.; De Oliveira, Gildasio S.
Abstract : Surv Anesthesiol 2016;60(2):72–73 The caudal block is the most commonly used regional anesthesia technique in children, but safety concerns previously raised have not been addressed. This investigation was undertaken to estimate the overall and specific incidence of complications associated with the performance of caudal blocks in a large cohort of children from multiple pediatric hospitals.